Discovering advancement in technology and mass media influence on gen Y male fashion consciousness - Arie Indra Gunawan; Adila Sosianika; Wahyu Rafdinal; Dede Ananta (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2022)
The growth of fashion development among male consumers in Indonesia is not supported by the increasing study on the male fashion segment. Therefore, it is necessary to understand the Generation Y male buying intention towards fashion products since Gen Y is the most prospective market. This study aims to investigate the factors that influence fashion consciousness among males in Indonesia by using self-identity, social media influence, changes in work practices, advancement in information technology, mass media influence variables, and the impact of fashion consciousness on buying intention. By employing quantitative research, the data collected uses a self-administered online questionnaire. The samples of this research are 227 respondents of Gen Y males with their profile data. This study uses partial squares structural equation modeling analysis with the smart PLS application to test the hypothesis. The findings of this study show that self-identity, social media influence, and mass media influence have a significant impact on fashion consciousness. Also, fashion consciousness has significant results on buying intention.